ANALISIS YURIDIS PEMBATALAN KEPUTUSAN KPU KABUPATEN MAHAKAM ULU BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 224/PHPU.BUP-XXIII/2025: Analisis Yuridis Pembatalan Keputusan Kpu Kabupaten Mahakam Ulu Berdasarkan Putusan Mahkamah Konstitusi Nomor 224/Phpu.Bup-Xxiii/2025 - Miftah, Muhammad; Prasetyo, Bayu; Elviandri (Jurnal Media Justitia Nusantara, 2025)
This study examines Constitutional Court Decision No. 224/PHPU.BUP-XXIII/2025, which annulled the results of the 2024 Mahakam Ulu Regency Regional Head Election due to proven serious violations of the principle of neutrality of the State Civil Apparatus (ASN) and abuse of authority by the incumbent regent in supporting his biological child’s candidacy for regional head. Employing a normative juridical method and a case study approach, the research focuses on analyzing the Constitutional Court’s legal reasoning and the juridical implications of annulling the decision of the Mahakam Ulu General Election Commission (KPU). The findings indicate that the actions of the public official in question met the criteria for structured, systematic, and massive (TSM) violations, significantly undermining electoral integrity and fairness. The Constitutional Court’s ruling is regarded as a form of constitutional protection of voters’ rights as well as a reinforcement of the rule of law and substantive democracy. This study underscores the urgency of reforming the electoral oversight system and strictly enforcing the principle of bureaucratic neutrality in the conduct of regional elections in Indonesia.